Evaluating Solvency II Implementation in Emerging Markets: A Quantitative Analysis of Algeria's Alliance Insurance Company (2017-2021) - Sid, Meriem; Bengana, Ismail; Mili, Khaled; Khababa, Nourredine; Benmoussa, Mohammed Soufiane (Journal of Posthumanism, 2025)
This study provides a comprehensive assessment of Solvency II quantitative requirements and their application in an emerging market context, focusing on Alliance Insurance Company, one of Algeria's leading insurers. Using a longitudinal analysis spanning 2017-2021, we evaluate the company's financial stability against international standards through rigorous calculation of Solvency Capital Requirements (SCR) and Minimum Capital Requirements (MCR). The research addresses a critical gap in understanding how European regulatory frameworks can be adapted to North African insurance markets. Our findings demonstrate that Alliance Insurance Company consistently maintained solvency capital ratios exceeding 500% and minimum solvency capital ratios above 1100% throughout the study period—substantially surpassing the 100% regulatory threshold. These exceptionally robust ratios indicate not only the company's strong financial position but also its resilience against market volatility and capacity to honor policyholder commitments under stress scenarios. The study contributes to regulatory policy discussions by demonstrating that Solvency II principles can be effectively applied in developing insurance markets, while highlighting adaptations necessary for local market conditions. These findings have significant implications for regulators, investors, and insurance practitioners in Algeria and comparable emerging markets seeking to strengthen financial stability standards.